Industrial uses of wood char - Kumar M.; Gupta R.C. (My University, 2025)
The quality and feasibility of wood char utilization in various industries are reported. Wood char provides fuel not only for cooking and domestic heating but also for many industrial purposes, such as manufacture of iron and some ferro-alloys, recovery of gold and other nonferrous metals from their leached solutions, manufacture of chemicals and medicines, burning of bricks and glass, and removal of toxic substances from their solutions. The selection of wood char for these purposes is made on the bases of its properties, such as chemical composition, reactivity heating value, electrical resistivity, adsorption capacity, and strength Quality, use, wood char.